Pengaruh Kompetensi Kepribadian Guru Terhadap Sikap Moderat Siswa di MI Al Huda Gempolsari Sidoarjo - Alawiyah, Siti Rimayatul; Ma’ruf, Ahmad; Kirom, Askhabul (CV. Satria Jaya, 2023)
MI AL Huda Gempolsari is an educational institution in Gempolsari Tanggulangin village, Sidoarjo. It is known that teachers at these institutions have social and personality competencies that are capable of being good examples for their students.The purpose of this study was to determine the effect of Teacher Personality (X) on Students' Moderate Attitudes (Y). This research method is quantitative with a causal associative approach. Data collection techniques using observation techniques, interviews, documentation and questionnaires (questionnaire). The sample in this study were 30 students using the Random Sampling technique. In this study using Multiple Linear Regression analysis. The results of this study can be concluded that the obtained F count is greater than F table (9.857 is greater than 3.32) with a significance less than 0.05 (0.001 is less than 0.05), it can be concluded that Personality Competence (X) jointly affect the Moderate Attitude of Students (Y). The regression coefficient value (Adjusted R Square) is 0.379 which means that Personality Competence (X) can influence Moderate Attitude (Y) by 37.9%, while the remaining 62.1% is explained by other factors which not researched.